THE POTENTIAL NATURAL HAZARDS TO BE CONSIDERED IN THE DESIGN AND EXPLOITATION OF THE AERIAL ROPE-WAY IN THE “GORA SOBOLINAYA” MOUNTAIN-SKIING RESORT (SOUTHERN PRIBAIKALIA, RUSSIA) - Kadetova, Alena; Kozireva, Elena (Bulletin of the Geological Society of Greece, 2010)
The paper deals with investigation of potential geological hazards to be taken into consideration in designing of the aerial rope-way, as well as problems of development of the recreation infrastructure in mountain lands with the complicated building conditions.